2022
DOI: 10.1159/000521771
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Quality of Life in Chronic Kidney Disease Stage 4–5 Patients Transitioning to Dialysis and Transplantation

Abstract: <b><i>Introduction:</i></b> Chronic kidney disease (CKD) has a profound effect on patients’ health-related quality of life (QoL). Longitudinal studies on QoL in CKD are scarce and have explored selected patients on renal replacement therapy (RRT). We studied the evolution of QoL in patients with advanced CKD transitioning to dialysis and transplantation in a prospective follow-up study. <b><i>Methods:</i></b> A total of 100 participants of the Chronic Arterial Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The concept and goals of modern dialysis are very clear: to improve the long-term survival rate and quality of life of dialysis patients as much as possible. [ 21 ] SF-36 is a widely used quantitative scale specifically designed to evaluate the quality of life of dialysis and kidney disease patients, and its results can reasonably and comprehensively reflect the quality of life of dialysis patients. [ 22 ] We used this scale to evaluate the quality of life of CAPD patients in our center, and the results showed that patients in the cognitive impairment group had lower scores than those in the control group with normal cognition in terms of physical function, general health, social function, emotional function, and mental health ( P < .05).…”
Section: Discussionmentioning
confidence: 99%
“…The concept and goals of modern dialysis are very clear: to improve the long-term survival rate and quality of life of dialysis patients as much as possible. [ 21 ] SF-36 is a widely used quantitative scale specifically designed to evaluate the quality of life of dialysis and kidney disease patients, and its results can reasonably and comprehensively reflect the quality of life of dialysis patients. [ 22 ] We used this scale to evaluate the quality of life of CAPD patients in our center, and the results showed that patients in the cognitive impairment group had lower scores than those in the control group with normal cognition in terms of physical function, general health, social function, emotional function, and mental health ( P < .05).…”
Section: Discussionmentioning
confidence: 99%
“…A score of 50 represents the normal reference value for each dimension and for the two global indices. The validity and reliability for SF 36 have been confirmed in patients with chronic kidney disease and in kidney transplant recipients [ 13 , 30 , 31 ]. Also, with regard to our sample of hemodialysis patients, the SF-36 showed good reliability (α = 0.92).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, nutritional factors, such as diabetes, hemoglobin [1,5], albumin, lipids profile [6], and creatinine level [11], were associated with QoL over time. Despite the associations, the precise impact of nutritional changes on the QoL trajectory of KTRs remains insufficiently explored in the current literature.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies, using tools such as the 36-Item Short-Form Health Survey (SF-36), have extensively analyzed recipients' QoL in the transition from hemodialysis or peritoneal dialysis to kidney transplantation and concluded that there was a significant improvement in the overall rating of QoL [ 5 , 6 ]. These studies predominantly reported enhancements in physical health components [ 7 , 8 ] and perceptions of overall health [ 2 , 8 , 9 ] following transplantation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation